International Monetary Fund Annual Report 1969. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1969)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1969. The report highlights that rapid expansion and financial imbalance were the main features of the performance of the world economy during 1968 and the first half of 1969. Output and trade in the industrial countries registered a sharp advance, imparting economic stimulus to the primary producing countries. Several of the industrial countries encountered severe balance-of-payments difficulties, and the international financial scene was marred by recurrent crises in foreign exchange markets.